2016
DOI: 10.1002/2015jd024129
|View full text |Cite
|
Sign up to set email alerts
|

Why do oceanic negative cloud‐to‐ground lightning exhibit larger peak current values?

Abstract: This study examines the temporal (monthly) and spatial climatology (2004–2010) of the first return stroke of the cloud‐to‐ground (CG) lightning flash peak current (Ip) across various land/water boundaries over the contiguous United States. Four regions are examined: the Gulf of Mexico (region 1), the Florida peninsula (region 2), Lake Michigan (region 3), and part of the U.S. Mid‐Atlantic (region 4). The crosss across the coastlines of regions 1, 2, and 4 show a gradual oceanward increase in the mean negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 82 publications
3
21
0
Order By: Relevance
“…Beirle et al () examined the global (60°S to 60°N) distributions of flash duration, footprint, and radiance using data from the OTD and LIS and found that these measures of flash strength were larger at marine locations than at continental locations. Their results were consistent with earlier analyses mentioned in Chronis et al (). For example, Lyons et al () found that peak currents for negative NLDN CG flashes were larger at ocean locations adjacent to the United States than at land locations.…”
Section: Discussionsupporting
confidence: 94%
“…Beirle et al () examined the global (60°S to 60°N) distributions of flash duration, footprint, and radiance using data from the OTD and LIS and found that these measures of flash strength were larger at marine locations than at continental locations. Their results were consistent with earlier analyses mentioned in Chronis et al (). For example, Lyons et al () found that peak currents for negative NLDN CG flashes were larger at ocean locations adjacent to the United States than at land locations.…”
Section: Discussionsupporting
confidence: 94%
“…The survey with Extremely Low-Frequency (ELF) electromagnetic radiation by Füllekrug et al (2002) also indicates that particularly strong negative strokes with charge moment changes > 2000 C km occur mostly over oceans. Chronis et al (2016) suggested that the relatively high strength of CG strokes over oceans is attributable to the enhanced potential of thunderstorms there. The observed dominance of negative sprites in some coastal areas near the tropics merits further investigation including ground-based observations from adjacent coast and a survey of lightning properties in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations indicate differences in continental and marine flashes. Boersma et al () found that continental flashes were ~1.6 times more productive than those over water, while Allen et al () estimated marine flashes to be twice as productive than continental flashes, consistent with earlier findings of more energetic flashes over oceans (Beirle et al, ; Chronis et al, ).…”
Section: Introductionmentioning
confidence: 99%